Identification of the trochlea with reference to the lacrimal caruncle, and its significance as a landmark in orbitofacial surgery. Issue 3 (March 2015) - Shin, Hyun Jin; Gil, Young-Chun; Shin, Kang-Jae; Shin, Ki Cheul; Koh, Ki-Seok; Song, Wu-Chul
Summary Purpose The purpose of this study was to identify the location of the trochlea in order to prevent injury during orbitofacial surgery and to determine the reliability of the lacrimal caruncle as a visible external landmark for the trochlea at the superomedial orbital rim. Methods Fifty-one orbits from 27 embalmed cadavers were dissected. The lacrimal caruncle and supraorbital notch/foramen were used as external and bony landmarks, respectively. The location of the trochlea was determined with respect to these structures, and the size of trochlea was measured. Results The trochlea was 3.6 mm wide and 5.6 mm long, with a flange breadth of 5.4 mm. The vertical distance from the apex of the lacrimal caruncle to the superolateral tip of the trochlea was 15.8 mm, and that from the top of the supraorbital notch/foramen to the bottom of the trochlea was 11.4 mm. As the coefficient of variation and standard deviation were smaller for DCT (11.5 and 1.8, respectively) than for DST (17.0 and 1.9, respectively), it appears that the lacrimal caruncle is a reliable landmark. Conclusions In contrast to the supraorbital notch, the lacrimal caruncle allows easy identification and serves as a reliable and visible external landmark for the prediction of the location of trochlea. The trochlea was located directly at 15.8 mm (i.e., approximately 1.5 cm) superior to the lacrimal caruncle. This anatomical study has yielded accurate measurements of the location of the trochlea, which may facilitate a safer orbitofacial surgery by preventing morbidity associated with trochlea injury.